verify
a=2/3,b=4/5,c=-5/6
a+(b+c)=(a+b)+c
Answers
Answered by
3
Answer:
Here is your Answer:
Step-by-step explanation:
Please mark brainliest
Attachments:
![](https://hi-static.z-dn.net/files/d10/d9d162108a0ad08e542dab52cddb4402.jpg)
Answered by
1
Step-by-step explanation:
a=2/3,b=4/5,c=-5/6
then,a+(b+c)=(a+b)+c
=>2/3+[4/5+(-5/6)]=(2/3+4/5)+(-5/6)
=>2/3+[24+(-25)/30]=(10+12/15)+(-5/6)
=>2/3+[24-25/30]=22/15+(-5/6)
=>2/3+[-1/30]=44+(-25)/30
=>20+(-1)/30=44-25/30
=>20-1/30=19/30
=>19/30=19/30(ANSWER)
Similar questions